The Effect of Environmental Performance, Foreign Ownership, and Firm Size on Corporate Social Responsibility Disclosure (Study on Energy Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 Period) - Suzan, Leny; Novianti, Silvia (UNIVERSITAS PAKUAN, 2023)
The information contained in the financial statements is the source of a decision that will be made by investors or potential investors, one of which is the disclosure of CSR. In the period 2018-2021, disclosure of CSR in energy sector companies listed on the IDX remains relatively low. Because there is still a lot of company data recorded as disclosing CSR below 50% of the total GRI Standards items, the implementation of CSR disclosure is still not perfect. There are various elements that impact the disclosure of CSR, particularly environmental performance, foreign ownership, and firm size. The goal of this research is to assess the simultaneous and partial influence of environmental performance, foreign ownership, and firm size on corporate social responsibility disclosure in energy sector companies listed on the IDX from 2018 to 2021. The methodology used in this study was quantitative, with sample selection using purposive sampling and a four-year observation period to obtain 36 sample units from nine organizations. For data analysis, panel data regression analysis with Eviews 12 software was employed. The findings revealed that environmental performance, foreign ownership, and firm size all had an impact on the disclosure of CSR. Environmental performance has a partial positive influence on CSRD, but foreign ownership and firm size have no impact.